A meta-analysis of proinflammatory cytokines in chronic heart failure. Issue 1 (8th September 2014) - Liu, Mao; Chen, Jian; Huang, Dan; Ke, Jianting; Wu, Wei
Abstract : Background: Previous studies suggested that inflammation was involved in chronic heart failure (CHF), but their sample sizes were small. Objective: To summarise the clinical cytokine data systematically and emphasise the importance of proinflammatory cytokines in the pathogenesis of CHF, we conducted a meta-analysis of relevant literatures. Methods: Articles about cytokines and CHF were searched in Pubmed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure and Chinese Wanfang Database. The pooled effects were measured by weighted mean difference (MD) and 95% CI, which were calculated by RevMan 5.1 software. Results: Finally, a total of 28 studies were included. Compared with normal control subjects, concentrations of tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1β and C reactive protein (CRP) in the peripheral blood in CHF patients are significantly increased. The overall MDs with 95% CIs for TNF-α, IL-6, CRP and IL-1β were 2.59 pg/ml (2.14∼3.05, p<0.00001), 5.49 pg/mL (4.68∼6.29, p<0.00001), 11.45 mg/dL (7.68∼15.23, p<0.00001) and 0.11 pg/mL (0.09∼0.14, p<0.00001). The mortality of elevated IL-6 group was significantly higher than control group (OR=6.73, 95% CI 2.39∼18.93, p=0.0003). Conclusions: Concentrations of TNF-α, IL-6, IL-1β and CRP are significantly higher in CHF patients than in control subjects. Proinflammatory cytokines play an import role in the pathogenesis of CHF.